Pattern of presentation of pressure ulcers in traumatic spinal cord injured patients in university college hospital, ibadan. (2011)
The neurosurgery division in University College Hospital (U.C.H.) admits approximately one traumatic spinal cord injured (SCI) patient per week, most of whom stay a minimum of 42 days on admission. A common complication in these patients is the development of pressure ulcers, which contributes to a longer hospital stay and increased hospital expenses. The purpose of this study was to investigate the pattern of presentation of pressure ulcers in patients on admission and to propose policies or protocols to reduce the incidence. It is a prospective study of traumatic SCI patients managed on the neurosurgery ward from January 2003 to June 2004. The data was analysed using descriptive' statistics. Sixty-seven patients were studied. The average hospital stay was 73 days. Thirteen (20%) of the patients were admitted with pressure ulcers, 32 (47-7%) developed it after admission. As much as 87-5% of pressure ulcers seen in the course of this study which occurred on admission in U.C.H. was in the first week of admission, 6-25% in the second week and the remaining 6-25% in the third week. Pressure ulcers were distributed as follows; 69% (42) in the sacral region, 18% (11) trochanteric, 5% (3) scalp, 1-5% (1) ankle, 1-5% (1) ischial tuberosity, the remaining 5% in other sites. Preventive measures for pressure ulcers consisted of basic skin care, pressure dispersion using fenestrated foams and alternating weight-bearing sites by regular turning. Pressure ulcers are commonest in the sacral and gluteal regions and tend to occur within the first week of admission in the neurosurgical wards.